Evaluasi Pengetahuan dan Kesiapsiagaan Tenaga Kesehatan serta Masyarakat dalam Penanganan Kegawatdaruratan Medis di Berbagai Fasilitas Kesehatan di Indonesia - Nabila, Nazua; Hasibuan, Abdurrozaq (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
The aim of this research is to assess the knowledge and abilities of health workers and the public in handling medical emergencies in various health facilities in Indonesia. This research uses a systematic literature review (SLR) method to assess the knowledge and skills of health workers and the community in handling medical emergencies in various health facilities in Indonesia. The SLR method was chosen because it can be used to identify, study, evaluate and comprehensively interpret all existing research on this topic. Several important conclusions can be drawn from declassified research findings from various medical emergency research texts. First, education and training play an important role in increasing the knowledge and readiness of health professionals and the public to face medical emergencies.